2003
DOI: 10.1093/sleep/26.5.596
|View full text |Cite
|
Sign up to set email alerts
|

Sleep-Disordered Breathing and Cognitive Impairment in Elderly Japanese-American Men

Abstract: Sleep-disordered breathing was associated with more drowsiness but not with poor performance on standardized cognitive tests used to screen for Alzheimer disease and other dementias in older persons. Because a healthy-participant effect may have contributed to this finding, more extensive cognitive testing may be necessary to reveal more subtle deficits from sleep-disordered breathing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
75
1
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(82 citation statements)
references
References 0 publications
4
75
1
2
Order By: Relevance
“…Such findings are not surprising as associations between OSA and some cognitive impairment are well established in multiple studies including sleep disorders clinic patients, older adults, patients with Alzheimer disease, and nursing home patients. [71][72][73][74][75][76][77][78][79] We also found that OSA treatment improves nighttime sleep in PD. 80 OSA treatment is therefore clinically indicated, as it may also reduce NMS impairment and improve quality of life.…”
supporting
confidence: 52%
“…Such findings are not surprising as associations between OSA and some cognitive impairment are well established in multiple studies including sleep disorders clinic patients, older adults, patients with Alzheimer disease, and nursing home patients. [71][72][73][74][75][76][77][78][79] We also found that OSA treatment improves nighttime sleep in PD. 80 OSA treatment is therefore clinically indicated, as it may also reduce NMS impairment and improve quality of life.…”
supporting
confidence: 52%
“…11,39 It is plausible that poor sleep differentially affects executive function by disrupting corticalsubcortical connections within the prefrontal cortex through vascular damage. 3,19,30,40 This study has several important limitations. We were unable to rule out potential selection bias; it is plausible that those with the greatest cognitive decline were less likely to return for a follow-up assessment.…”
Section: Resultsmentioning
confidence: 96%
“…Of the remaining 1,473, 49% completed the PSG. 11 Of these 718 men, 502 died through 2010, and, of these, 167 were included in the autopsy substudy and in this analysis. Data were made available through the National Institute on Aging.…”
Section: Methods Study Population the Honolulu-asia Agingmentioning
confidence: 99%
“…Details of the PSG protocol have been described. 11 We examined apnea-hypopnea index (AHI), duration of apnea or hypopnea, duration of hypoxemia, minimum oxygen saturation during REM and non-REM sleep, duration of slow-wave (SWS, non-REM stage N3) and REM sleep, and arousals. SWS scoring was based on strict amplitude and frequency criteria.…”
Section: Methods Study Population the Honolulu-asia Agingmentioning
confidence: 99%